Ultrasound Guided Sciatic Nerve Block Combined with Adductor Canal Block Virsus Local Analgesic Infiltration to Control the Pain after Total Knee Arthroplasty - Eldegwy, Magdy H.; Negm, Mohamed A. (Highlights on Medicine and Medical Research Vol. 4, 2021)
Background: A combined adductor canal block (ACB) and sciatic nerve block (SNB) is new different way to achieve an efficient postoperative analgesia after total knee replacement (TKR) that spares the weakness of quadriceps femoris muscle. We compared ultrasound guided combined adductor canal and sciatic nerve blocks that performed by anesthesiologist with surgeon applied local anesthetic infiltration for analgesic efficacy within the first 24 h after TKR. This prospective randomized controlled trial aimed to evaluate the efficiency and safety of the combined adductor canal with sciatic nerve blocks versus local analgesic infiltration alone for pain control after total knee replacement. Patients and Methods: Forty patients (ASA II, and III), undergoing unilateral total knee replacement, were randomly and allocated to two groups (20 patients each), block group (ACB+SNB): The patient received US- guided adductor canal block combined with sciatic nerve block, local group (LAI): Patient received local analgesic injection (LAI) to entire of the knee joint. The primary outcomes were postoperative visual analogue scale (VAS) at rest and with movement, first request of analgesics and 24 h total consumption of morphine. Secondary outcome measures included sedation score and side effects associated with morphine consumption like nausea, vomiting. Results: There was a significant reduction in postoperative morphine consumption, VAS, nausea and vomiting and sedation at 12 h in local group. There were no complications attributable to the ACB or SNB blocks. Conclusion: Combined adductor canal with sciatic nerve blocks could significantly reduce VAS scores, morphine consumption, and first request for analgesia in comparison with local analgesic infiltration alone following TKA. Additionally, there is a lower incidence of sedation, nausea and vomiting in the combined blocks group.